2016
DOI: 10.1007/s12195-016-0460-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of the Tumor Stromal Microenvironment Probed In Vitro and Ex Vivo by In Situ-Calibrated Optical Trap-Based Active Microrheology

Abstract: One of the hallmarks of the malignant transformation of epithelial tissue is the modulation of stromal components of the microenvironment. In particular, aberrant extracellular matrix (ECM) remodeling and stiffening enhances tumor growth and survival and promotes metastasis. Type I collagen is one of the major ECM components. It serves as a scaffold protein in the stroma contributing to the tissue’s mechanical properties, imparting tensile strength and rigidity to tissues such as those of the skin, tendons, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 108 publications
4
39
0
Order By: Relevance
“…Drawing on polymer physics, we can further classify the cell rheological properties by examining the power law frequency dependence jG*j ∝ ω b . Flexible polymer networks are predicted to have complex moduli with b = 0.5, whereas b = 0.75 for semiflexible polymers (16). We observed that for high frequencies (400 to 15,000 Hz), the magnitudes jG*j of cells, near-ECM and far-ECM each fit to power laws with different exponents (i.e., slopes) b ranging from 0.46 to 0.70 (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Drawing on polymer physics, we can further classify the cell rheological properties by examining the power law frequency dependence jG*j ∝ ω b . Flexible polymer networks are predicted to have complex moduli with b = 0.5, whereas b = 0.75 for semiflexible polymers (16). We observed that for high frequencies (400 to 15,000 Hz), the magnitudes jG*j of cells, near-ECM and far-ECM each fit to power laws with different exponents (i.e., slopes) b ranging from 0.46 to 0.70 (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Formulaic explanations allow us to draw from our understanding of non-Newtonian fluids to model rheological properties of tissue (12)(13)(14). One property of tissues that emerges from non-Newtonian fluid mechanics is that viscoelasticity (complex moduli [G′*]) obeys frequency-dependent power laws, jG*(ω)j = Aω B , where the dependence B varies for different frequency regimes and different cell types (12)(13)(14)(15)(16). Gaining a mechanistic understanding of how these dynamics influence physiological and pathological mechanobiology thus requires quantitative measurements of cells and ECM in context.…”
mentioning
confidence: 99%
“…In addition to differences in the magnitude of the complex modulus, we observed a difference in frequency dependence between the aligned gels and unaligned gels. Power law dependence of the complex modulus on frequency has been previously observed in a number of biomaterials, and various models have been proposed to explain this behavior according to the underlying dynamics of the constituent polymers (47)(48)(49)(50). In fibrillar collagen gels polymerized at 2 mg/ml or 6 mg/ml at 4°C or 37°C, we previously observed power law exponents ranging from 0.66 -0.74 (48), in the range predicted for a semi-flexible polymer network.…”
Section: Discussionmentioning
confidence: 57%
“…For complete experimental details, see (48,59,60). Our home-built setup consists of a 1064 nm trapping beam steered by an acousto-optic deflector to oscillate the trap and a stationary 975 nm detection beam that is coupled into and colocated with the trap with a dichroic before being sent into the backport of an inverted microscope with a long working distance water objective and a high NA condenser.…”
Section: Optical Tweezer-based Microrheologymentioning
confidence: 99%
“…In the invited talk for this session, Dr. Kandice Tanner from the U.S. National Institutes of Health discussed the applications of local viscoelastic properties of tumors and extracellular matrix surrounding those tumors. [36][37][38] Her group is searching for the understanding of mechanisms of metastasis, which were linked to local mechanical properties of cells and tissues. To quantify those small mechanical forces, they use optical tweezers and fluctuation correlation analysis.…”
Section: Cell Biomechanicsmentioning
confidence: 99%